Functional magnetic resonance imaging (fMRI) changes and saliva production associated with acupuncture at LI-2 acupuncture point: a randomized controlled study - Holodny Andrei I; Hou Bob L; Deng Gary; Cassileth Barrie R (BMC, 2008)
Abstract Background Clinical studies suggest that acupuncture can stimulate saliva production and reduce xerostomia (dry mouth). We were interested in exploring the neuronal substrates involved in such responses. Methods In a randomized, sham acupuncture controlled, subject blinded trial, twenty healthy volunteers received true and sham acupuncture in random order. Cortical regions that were activated or deactivated during the interventions were evaluated by functional magnetic resonance imaging (fMRI). Saliva production was also measured. Results Unilateral manual acupuncture stimulation at LI-2, a point commonly used in clinical practice to treat xerostomia, was associated with bilateral activation of the insula and adjacent operculum. Sham acupuncture at an adjacent site induced neither activation nor deactivation. True acupuncture induced more saliva production than sham acupuncture. Conclusion Acupuncture at LI-2 was associated with neuronal activations absent during sham acupuncture stimulation. Neuroimaging signal changes appear correlated to saliva production.